THE IDIOMATIC CONSTRUCTIONS OF ”BAPAK” IN BAHASA INDONESIA - Danang Satria Nugraha (Universitas Negeri Makassar, 2020)
This research aimed to describe the idiomatic constructions of lexeme of BAPAK in Bahasa Indonesia (BI). The language description method used in this study was adopted from the semantic analysis model suggested by Langlotz (2006). The sources of the data were the corpus websites that provided the BI data-set. Observation was used to collect the data and a distributional technique was used to analyze the data. The results of the analysis described that the idiomatic constructions of lexeme of BAPAK had two patterns of constructions and three types of proposition that were embedded in them. Thus, it can be inferred that the idiomatic constructions of BAPAK can be described through their structural patterns and types of proposition.